A large-eddy simulation study of the stable pbl - Sinhori, Natalia P.; Furtado, Taisson I.; Reyes, Igor N.; Rizza, Umberto; Carvalho, Jonas C. (Ciência e Natura, 2007)
A Large-Eddy Simulation Study of the Stable PBL